2005
DOI: 10.1007/s10750-005-5441-2
|View full text |Cite
|
Sign up to set email alerts
|

Associated community with the zoanthid Palythoa caribaeorum (Duchassaing & Michelotti, 1860) (Cnidaria, Anthozoa) from littoral of Pernambuco, Brazil

Abstract: The community associated with the zoanthid Palythoa caribaeorum on shores (Porto de Galinhas and Guadalupe) in northeastern Brazil were analysed. Seasonal samples (dry and wet) were made in both beaches throughout one year. This preliminary study identified 28 taxa and recognized two modes of existence, endobionts (three taxa) and hypobionts (25 taxa). Among hypobionts two patterns of ecological relationships were found: those fixed to the rocky substrata or on the base of the zoanthid colony (11 taxa) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 6 publications
0
22
1
1
Order By: Relevance
“…The results found in the study conducted by Pèrez et al (2005) showed a low number of epibenthic mollusc species associated to this zoanthid. One of the possible explanations for this negative relationship is the low structural complexity offered by this zoanthid, which forms extensive and flat dense covers with a high production of mucus.…”
Section: Discussionmentioning
confidence: 71%
“…The results found in the study conducted by Pèrez et al (2005) showed a low number of epibenthic mollusc species associated to this zoanthid. One of the possible explanations for this negative relationship is the low structural complexity offered by this zoanthid, which forms extensive and flat dense covers with a high production of mucus.…”
Section: Discussionmentioning
confidence: 71%
“…As observed from other studies, P. caribaeorum dominated rocky shores throughout an extensive area of the Brazilian coast (Villaça and Pitombo 1997, Castro et al 1999, OigmanPszczol et al 2004). These reports indicate its presence from the Northeastern (Pérez et al 2005) to the Southeastern coast (Boscolo and Silveira 2005), including oceanic islands (Edwards and Lubbock 1983, Gasparini and Floeter 2001), and there is always a relationship with the depth gradient, something about 2 to 8 meters, and also with a weak/intermediate hydrodynamic regime. Despite a wide distribution, its dominance over reef fish communities were not investigated until now.…”
Section: Discussionmentioning
confidence: 97%
“…It is recognized as an aggressive competitor against neighbors for vital resources (Suchanek andGreen 1981, Sorokin 1995) and space (Lang 1973, Bak et al 1982 and to be tolerant to high environmental variability (Cooke 1976, Sebens 1982, Sorokin 1991, Kemp et al 2006. Nevertheless, there are still a lot of ecological processes encompassing its dominance which is less investigated, like the effects it could fulfill on the structure of reef communities (Sheppard 1982, Carlon and Olson 1993, Acosta et al 2005, Boscolo and Silveira 2005, Pérez et al 2005. The P. caribaeorum tissue contains a powerful high molecular weight toxin known as palytoxin (PTX) (Gleibs et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified such organisms hosting other organisms, e.g., sponges (Ribeiro et al 2003), hydroids (Genzano 2001), gorgonians (Kumagai 2008) and zoanthids (Pérez et al 2005); however, few studies have evaluated the importance of the habitat structure provided by such organisms (Vytopil and Willis 2001).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%